2017
DOI: 10.5899/2017/dea-00146
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Efficiency of commercial Tunisian Banks using Fuzzy Data Envelopment Analysis

Abstract: The banking sector is of great importance to Tunisian's economy. Major commercial banks continue to spend high proportion of their budgets on new technologies and innovation in order to satisfy their customers and enhance their competitiveness. Consequently, performance analysis has become part of their management practices.This paper aims to evaluate the efficiency of commercial Tunisian banks in terms of several crisp and imprecise data. Two approaches of fuzzy data envelopment analysis (FDEA), the possibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
6
1
Order By: Relevance
“…Size was found to be significant and negatively related to technical efficiency in all bootstrap regressions. Hence, unlike Ayadi (2014) and Chenini and Jarboui (2018) who found that bank size is insignificant in explaining technical efficiency over the period of 2000, and contrary to Ben Romdhane (2013 and Tlig and Hamed (2017), we can conclude that larger banks in terms of total assets are characterized by being less technically efficient. Thus, larger banks in Tunisia are likely more difficult to manage due to the bureaucracy and mismanagement of public banks.…”
Section: Table 5 Comparison Of Average Original and Bias-corrected Technical Efficiency Of Banks By Type Of Ownership Before And After Thcontrasting
confidence: 94%
“…Size was found to be significant and negatively related to technical efficiency in all bootstrap regressions. Hence, unlike Ayadi (2014) and Chenini and Jarboui (2018) who found that bank size is insignificant in explaining technical efficiency over the period of 2000, and contrary to Ben Romdhane (2013 and Tlig and Hamed (2017), we can conclude that larger banks in terms of total assets are characterized by being less technically efficient. Thus, larger banks in Tunisia are likely more difficult to manage due to the bureaucracy and mismanagement of public banks.…”
Section: Table 5 Comparison Of Average Original and Bias-corrected Technical Efficiency Of Banks By Type Of Ownership Before And After Thcontrasting
confidence: 94%
“…The findings show that the efficiency results of many PuSBs varied with the variation in α during the selected period [18]. Similarly, Tlig and ben Hamed [19] evaluated the efficiency of commercial Tunisian banks in terms of several crisp and imprecise datasets. Fuzzy data envelopment analysis (FDEA), the possibility approach, and an approach based on relations between fuzzy numbers (BRONF) were used to obtain the efficiency score of each bank.…”
Section: Literature Overviewmentioning
confidence: 90%
“…Fuzzy data envelopment analysis (FDEA), the possibility approach, and an approach based on relations between fuzzy numbers (BRONF) were used to obtain the efficiency score of each bank. The results show that, in a competitive environment, non-financial inputs and outputs should be taken into account in order to obtain credible and realistic efficiency scores [19]. Further, fully fuzzy cost-efficiency (FFCE) and fully fuzzy revenue-efficiency (FFRE) models, where input-output data and prices include uncertainty of fuzzy forms, were proposed and compared with existing approaches for proving their effectiveness in real-world situations [20].…”
Section: Literature Overviewmentioning
confidence: 99%
“…6) Tlig and Hamed [25], estimate the efficiency of Tunisian banks by using DEA in the case of imprecise data (fuzzy data).they use fuzzy DEA by using two approaches, possibility and based on relations between fuzzy numbers (BRONF) approach. They evaluate the efficiency score of Tunisian banks for the period 2011-2013 by possibility and BRONF approaches.…”
Section: B Dea Applications Papers In Banking Sector Publish In Yearmentioning
confidence: 99%